Neural correlates of autobiographical memory retrieval in children and adults. Issue 4 (21st April 2017) - Bauer, Patricia J.; Pathman, Thanujeni; Inman, Cory; Campanella, Carolina; Hamann, Stephan
ABSTRACT: Autobiographical memory (AM) is a critically important form of memory for life events that undergoes substantial developmental changes from childhood to adulthood. Relatively little is known regarding the functional neural correlates of AM retrieval in children as assessed with fMRI, and how they may differ from adults. We investigated this question with 14 children ages 8–11 years and 14 adults ages 19–30 years, contrasting AM retrieval with semantic memory (SM) retrieval. During scanning, participants were cued by verbal prompts to retrieve previously selected recent AMs or to verify semantic properties of words. As predicted, both groups showed AM retrieval-related increased activation in regions implicated in prior studies, including bilateral hippocampus, and prefrontal, posterior cingulate, and parietal cortices. Adults showed greater activation in the hippocampal/parahippocampal region as well as prefrontal and parietal cortex, relative to children; age-related differences were most prominent in the first 8 sec versus the second 8 sec of AM retrieval and when AM retrieval was contrasted with semantic retrieval. This study is the first to characterise similarities and differences during AM retrieval in children and adults using fMRI.